2017
DOI: 10.14716/ijtech.v8i5.861
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Behavior of Hybrid Structural Insulated Panels under Pure Bending Load

Abstract: This paper presents the structural behavior of newly-developed hybrid structural insulated panels (SIPs) formed by incorporating lignocellulosic composites-jute fiber composite (JFC) and medium-density fiber (MDF)-as intermediate layers between aluminum skin and an expanded polystyrene (EPS) core. The investigation was conducted as an experimental work. A four-point bending load was performed to create pure bending conditions, and the samples were prepared in accordance with ASTM C 393-00 standards. Testing wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(21 reference statements)
0
5
0
1
Order By: Relevance
“…The theoretical concept of this new hybrid sandwich panel was comprehensively developed by Fajrin (2015). Further, Fajrin et al (2016Fajrin et al ( , 2017 experimentally investigated the suitability of the hybrid sandwich panels for structural applications and found that they can be applied for the structure under flexural or in-plane shear loading. Essentially, there are two main criteria in the selection of core materials used in sandwich panel structure; the design criteria and the specific application (Davies, 2008), hence all lightweight materials may be used for the core.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical concept of this new hybrid sandwich panel was comprehensively developed by Fajrin (2015). Further, Fajrin et al (2016Fajrin et al ( , 2017 experimentally investigated the suitability of the hybrid sandwich panels for structural applications and found that they can be applied for the structure under flexural or in-plane shear loading. Essentially, there are two main criteria in the selection of core materials used in sandwich panel structure; the design criteria and the specific application (Davies, 2008), hence all lightweight materials may be used for the core.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, this emerging material was extensively investigated in relation to mechanical engineering applications, but it now has extended to other engineering fields such as in civil engineering. Many studies have also been focused on developing building components, among these was the hybrid structures for structural applications as reported by Fajrin [3] and Fajrin et al [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Another study was carried out by Do et al (2013) on the ultimate limit state assessment of stiffened panel structures for extremely large ore carriers. The alternative hybrid structural panel was elaborated on by Fajrin et al (2017) in terms of its structural behavior under a pure bending load. Finally, an analytical model is developed by Benbouras et al (2017) under three-point bending for symmetric laminated beams.…”
Section: Introductionmentioning
confidence: 99%